Implementation of Downstream Tourism Policy in Riau Islands Province: Penta Helix Review - Akhdiva Elfi Istiqoh; Ida Rahayu; Eki Darmawan; Adhe Fadli Farhan; Azrul Asyikin; Rio Ramadan (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2026)
The purpose of this study is to analyze the implementation of downstream tourism policies, as well as examine the role of actors in the framework of the Penta Helix, which includes the government, academia, the business world, the community, and the media. This study uses a descriptive qualitative approach, with primary data obtained through in-depth interviews and observations, as well as secondary data from regional policy documents such as RPJMD and RIPPDA. The analysis was carried out using thematic analysis techniques, focusing on the stages of planning, implementation, and the dynamics of collaboration between actors. The results of the study show that the implementation of downstream tourism policy in the Riau Islands has been running through cross-sector programs oriented towards strengthening the creative economy, training human resources, and digitizing destination promotion. The government plays the role of policy director and main facilitator, while academics, the business world, the community, and the media have begun to collaborate in supporting the implementation of the policy. However, the level of coordination between actors still needs to be strengthened so that collaboration is more functional and sustainable. In conclusion, the application of the Penta Helix model in the implementation of downstream tourism policies in Riau Islands Province has shown significant progress towards collaborative governance. Effective collaboration is the main key in ensuring policy sustainability and optimizing the tourism potential of this archipelagic region.